Antitrust policy in Serbia: Regulatory framework and enforcement mechanism - Dragan Loncar; Sinisa Molisevic (Journal of Contemporary Economic and Business Issues, 2015)
The main goal of this academic paper is to provide an assessment of the current Antitrust regulatory framework in Serbia along with an analysis of Antitrust Commission practice in this field. This paper comprises of five sections. The first section focuses on the general provisions of Antitrust policy. The second part elaborates four segments of Antitrust policy. The third section gives an insight into the development of Serbian regulatory framework, as well as an overview of the current situation. In the fourth segment the analysis of practices used by Antitrust Commission based on the most important indicators is given. Conclusions and directions for further research are given in the last section.
Keywords: K20; K21; K210; 330; competition; Antitrust Law; Antitrust policy; Antitrust Commission